Zbornik povzetkov študentskih del / 7. letna konferenca mehatronike 2018, Maribor - Marina Bajić; Župerl, Uroš; Hace, Aleš (2018)
Book of Abstracts, Student Projects / 7th Annual Conference of Mechatronics 2018, Maribor. The Faculty of Electrical Engineering, Computer Science and Informatics (FERI) and the Faculty of Mechanical Engineering (FS) of the University of Maribor (UM) are the only ones in Slovenia to conduct quality independent study programs of Mechatronics at undergraduate university and higher professional level 1 and at postgraduate master's level 2 studies. The engineer of Mechatronics is in the domestic industry, and even more so in our neighborhood, an extraordinary and increasingly sought-after profile, and the experts in this field are involved in the production and development of state-of-the-art mechatronics products. The study programs of Mechatronics at the University of Maribor are distinguished by a project-oriented method of education, where students work in groups on various practical mechatronic problems. The results of their project work are presented by students at the end of the school year at the Mechatronics Summer Conference. Thus, this year, at the conference organized 28.6.2018 together, 26 projects, of which 9 projects are students of the higher education program, 9 projects are students of the university undergraduate study program, and 8 projects are students of the postgraduate master's study program. Summaries of these projects have been gathered in the present encyclopedia, where basic information is shown, and you can find out more details at the conference. All projects are interesting and therefore we invite you on behalf of the FERI and FS organizers to take part in this year's Annual Mechatronic Conference!
Keywords: mechatronics; robotics; automation; industry; student projects